Hypertrophic obstructive cardiomyopathy-alcohol septal ablation vs. myectomy: a meta-analysis - Mahboob Alam; Hisham Dokainish; Nasser Lakkis (2009)
AimsOur purpose is to conduct a meta-analysis of all published studies comparing alcohol septal ablation (ASA) and myectomy (MM) for drug refractory hypertrophic obstructive cardiomyopathy (HOCM). Alcohol septal ablation is a less invasive alternative to MM for relief of symptoms in patients with drug refractory HOCM.